Simplify the following expression using PEMDAS
6 + 3 x 42 – 7 PLEASE SHOW THE DIFFERENTS STEPT

Question|Rated good

Asked 2/20/2011 4:59:02 PM

Updated 5/31/2014 4:54:24 PM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|ambrosio_09|Points 1025|

Expert answered|ambrosio_09|Points 1025|

Expert answered|ambrosio_09|Points 1025|

Question|Rated good

Asked 2/20/2011 4:59:02 PM

Updated 5/31/2014 4:54:24 PM

1 Answer/Comment

Rating

8

3 + 4[(8 ÷ 2) + 3];

3 + 4[4 + 3];

3 + 4[7];

3 + 28 = 31

3 + 4[4 + 3];

3 + 4[7];

3 + 28 = 31

Added 5/31/2014 4:54:24 PM

This answer has been confirmed as correct and helpful.

4x + 18 = 10 User: 12x – 17 = -41 **Weegy:** 12x-17=-41 (add 17 to both sides), (More)

Question

Expert Answered

Updated 12/28/2018 10:22:07 AM

3 Answers/Comments

4x + 18 = 10

4x = 10 - 18

4x = -8

x = -8/4

x = -2

4x = 10 - 18

4x = -8

x = -8/4

x = -2

Added 8/16/2015 5:57:12 AM

This answer has been confirmed as correct and helpful.

12x – 17 = -41

12x = -41 + 17

12x = -24

x = -24/12

x = -2

12x = -41 + 17

12x = -24

x = -24/12

x = -2

Added 8/16/2015 5:57:41 AM

This answer has been confirmed as correct and helpful.

Let's solve your equation step-by-step.

12x 17= 41

Step 1: Add +17 to both sides.

12x 17+17= 41+17

12x= 24

Step 2: Divide both sides by 12.

12x12= 24

12x= 2

Answer:

x= 2

12x 17= 41

Step 1: Add +17 to both sides.

12x 17+17= 41+17

12x= 24

Step 2: Divide both sides by 12.

12x12= 24

12x= 2

Answer:

x= 2

Added 12/28/2018 10:22:07 AM

Simplify the following expressions using PEMDAS 6 + 3 x 42 – 7 Please show steps with answer.

Question

Updated 102 days ago|10/20/2022 1:18:03 AM

2 Answers/Comments

6 + 3 x 42 – 7;

6 + 126 - 7;

132 - 7 = 125

6 + 126 - 7;

132 - 7 = 125

Added 6/1/2014 11:46:09 AM

This answer has been confirmed as correct and helpful.

6 + 3 x 42 – 7 = 125

Since there's only three operation in that expression and if we need to simplify that through using PEMDAS rule then first we have to multiply the numbers with multiplication operation, follows by addition then subtraction and we'll arrive to a correct answer.

Since there's only three operation in that expression and if we need to simplify that through using PEMDAS rule then first we have to multiply the numbers with multiplication operation, follows by addition then subtraction and we'll arrive to a correct answer.

Added 102 days ago|10/20/2022 1:18:03 AM

PLEASE USE THE P.E.M.D.A.S TO SIMPLIFY THIS PROBLEM: 6 + 3 x 42 – 7 **Weegy:** 6 + 3 x 42 – 7; = 6 + 126 -7; = 125
(More)

Question

Expert Answered

Updated 5/31/2014 4:55:04 PM

0 Answers/Comments

Simplify: 4(3 – x) – 3(-5 – 12x)

Question

Updated 12/29/2018 8:50:18 PM

2 Answers/Comments

4(3 – x) – 3(-5 – 12x)

= 12 - 4x + 15 + 36x

= 32x + 27

= 12 - 4x + 15 + 36x

= 32x + 27

Added 5/14/2018 11:48:39 AM

This answer has been confirmed as correct and helpful.

Solve by using PEMDAS: 6 X 3 + 10/2. **Weegy:**
6 X 3 + 10/2
= 18 + 10/2
= 18 + 5
= 23
(More)

Question

Expert Answered

Updated 7/16/2014 11:03:21 AM

1 Answer/Comment

37,256,809

questions answered

There are no comments.